Reversible, Selective, Ultrawide‐Range Variable Stiffness Control by Spatial Micro‐Water Molecule Manipulation - Inho Ha; Minwoo Kim; Kyun Kyu Kim; Sukjoon Hong; Hyunmin Cho; Jinhyeong Kwon; Seonggeun Han; Yeosang Yoon; Phillip Won; Seung Hwan Ko (Advanced Science, 2021)
Abstract Evolution has decided to gift an articular structure to vertebrates, but not to invertebrates, owing to their distinct survival strategies. An articular structure permits kinematic motion in creatures. However, it is inappropriate for creatures whose survival strategy depends on the high deformability of their body. Accordingly, a material in which the presence of the articular structure can be altered, allowing the use of two contradictory strategies, will be advantageous in diverse dynamic applications. Herein, spatial micro‐water molecule manipulation, termed engineering on variable occupation of water (EVO), that is used to realize a material with dual mechanical modes that exhibit extreme differences in stiffness is introduced. A transparent and homogeneous soft material (110 kPa) reversibly converts to an opaque material embodying a mechanical gradient (ranging from 1 GPa to 1 MPa) by on‐demand switching. Intensive theoretical analysis of EVO yields the design of spatial transformation scheme. The EVO gel accomplishes kinematic motion planning and shows great promise for multimodal kinematics. This approach paves the way for the development and application of smart functional materials.